44.7k views
5 votes
If f(x) = 8x+9, g(x) = -6x and h(x) = 2x^2 evaluate

(gh)(x)

User Skygeek
by
5.4k points

1 Answer

6 votes

Answer:


\boxed {\boxed {\sf (gh)(x)=-12x^3}}

Explanation:

We are asked to evaluate (gh)(x). This is an operation on functions. Basically, we will multiply g(x) by h(x).


(gh)(x)= g(x) * h(x)

The functions are:

  • g(x) = -6x
  • h(x) = 2x²

We can substitute these into the formula.


(gh)(x)=(-6x) * (2x^2)

Multiply. Remember, both the coefficients and variables are multiplied.


(gh)(x)=(-6*2)(x*x^2)


(gh)(x)=(-12)(x^3)


(gh)(x)=-12x^3

(gh)(x) is equal to -12x³

User Ahawkins
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.